Improvement of selected chemical and biological properties of acid soil amended with fortified effective microorganisms - Rawichandran, Darshini (2022)
Soil acidification, a major cause of soil deterioration, severely influences soil production and the ecosystem. The contemporary agriculture industry dominates most of Malaysia’s croplands, with intense cultivation and heavy chemical fertilizer input. Soil acidity has the potential to alter the structure and diversity of soil microbial communities. Organic additions in agriculture have the ability to boost crop output and improve soil health. In that context, soil amendments linked with beneficial microbes have been chosen as more advantageous in terms of gaining access to input and adding value to land holdings. Hence, this study was conducted to improve soil productivity through soil amendments by impacting the microbial population’s assemblies and to identify the effective ratio of formulated soil amendments in controlled environment. Furthermore, this study was also conducted to determine the effect of formulated soil amendments on the soil’s physical, chemical, and biological properties. Firstly, the EM was prepared using the standard protocol. Then, formulated soil amendments were done by mixing Effective Microorganisms (EM) with “X” materials, Perlite, Coconut Shell Ash (CSA), and “Y” sources before they can be incubated in 250 g of soil in a round disposal container for 30 days. Two different rates were applied during this application, which were 50% and 100% based on the recommended rate from the literature review. The incubation study demonstrated the effectiveness of soil amendments in ameliorating acidity by increasing the soil pH, EC, ECEC, and macronutrients with the decrease of exchangeable acidity performed at 50% application than 100%. At 50 % soil amendment application, the colony forming units were highest from T0 to T4 than 100% soil amendment application. The isolates from the culturing medium, T0 to T4 were yeasts, and T2 bacteria were successfully sequenced and identified to classify the closely related strains respectively. Most of the isolated treatments are gram-negative. However, treatment 2 found in the soil amendment is gram-positive. This study found that the application of soil amendments at 50% increased the soil microbial diversity, which significantly enhanced the soil biological properties. This interaction demonstrating that fungi generally exhibit wider pH ranges for optimal growth of the genus Ascomycota. Our findings revealed that observed fungi is better equipped to withstand environmental stress and utilize many resources, increasing its dominance in acidic soils. Further correlation analysis indicated that exchangeable Mg was positively correlated with the relative abundance of microbe. This observation can potentially occur when Mg ions promote nitrification activity in yeasts by altering the enzyme activities, and this will explains the highly positive relationship between Mg concentration and fungal population. The exchangeable Na and Ca were negatively correlated with the relative abundance. In the present study, the K content increased in response to the decreasing pH value, and based on this, the relative abundance of Actinobacteria was highest in high acidity soils. As known, actinobacteria is a type of saprophytic bacteria which are present in the soil that has the ability to decompose complex substrates. Generally, higher number of beneficial yeast strains were successfully isolated from the formulated soil amendments that has been treated with EM from T0 to T4 except for T2 that contain a bacterial strain. The isolated fungi from this study can be utilized in promoting soil fertility with an appropriate application rate. Utilization of waste in formulating soil amendments can help to reduce waste generation and environmental pollution. In general, this study indicates the importance of soil amendments in promoting beneficial microbes in acidic soil.